2007
DOI: 10.2214/ajr.05.0469
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Robotic Arm to Perform Remote Abdominal Telesonography

Abstract: Robotic telesonography can be used for reliable diagnosis without moving the patient. No false diagnoses were made in this study. A bandwidth of 250 Kbps via integrated services digital network or satellite is required for reliable diagnosis. Such a system can provide diagnostic information that is currently unavailable in isolated or inaccessible areas and on rescue vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 11 publications
2
44
0
Order By: Relevance
“…1 This confirms that use of tele-echography or remote guidance of an echographic probe is possible for diagnostics and our study showed that it was possible for interventional echography.…”
Section: Discussionsupporting
confidence: 87%
“…1 This confirms that use of tele-echography or remote guidance of an echographic probe is possible for diagnostics and our study showed that it was possible for interventional echography.…”
Section: Discussionsupporting
confidence: 87%
“…Telesonography has been developed for specific situations such as isolated islands, ships or even spacecraft, with for example the Melody telesonography robotic arm [14]. This technique lets the remote radiologist ''touch'' the patient via a balanced robotic arm holding the probe, and visualize real time ultrasound video images.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be feasible in the prehospital setting [4,5], austere environments [6], by ship officers on merchant ships [7], outer space [8], and from lower acuity hospitals to trauma centers [9,10]. Studies have shown that using robots, image acquisition can be done remotely as well [11][12][13][14][15][16]. In addition, one could imagine the potential in other settings where ultrasound machines exist, but usually without much educational or clinical oversight, such as underdeveloped countries or community hospitals without an ultrasound expert readily on hand with difficult cases.…”
Section: Discussionmentioning
confidence: 99%